El intersticio, enlace de interacciones (2017)
"This study parts from the premise of the appearance of a elevated massive transportation system through the Avenida Caracas in Bogotá. Specifically, this project consists in a building that is located in the 65 street and that connects the city across east and west creating a cultural and educative axis, joining the east mountains with the public park El Lago. To develop the project, the building allowed a CLAN ( Local Center of arts for the chilhood and youth) so it became the piece that articulates and strengthens the new cultural and educative axis." -- Tomado del Formato de Documento de Grado.